2023
DOI: 10.1186/s12891-023-06907-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidant enzymes in spinal stenosis patients with lumbar disc herniation: correlation with degeneration severity and spinal fusion rate

Youfeng Guo,
Yu Zhou,
Haihong Zhao
et al.

Abstract: Objective To determine whether superoxide dismutase (SOD) and glutathione reductase (GR) correlated with the intervertebral disc degeneration (IDD) severity and the postoperative spinal fusion rate in lumbar spinal stenosis patients accompanied with lumbar disc herniation. Methods This retrospective study investigated 310 cases of posterior lumbar decompression and fusion. The cumulative grade was calculated by adding the pfirrmann grades of all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Our study did not find significant involvement of the glutathione antioxidant system in disc degeneration. In contrast, Bakirezer et al [ 12 ] and Gu et al [ 28 ] reported significantly lower serum glutathione levels in patients with LDD than in healthy individuals or in those with less degeneration. Additionally, an in vitro disc cell model showed that the harmful effects of hydrogen peroxide could be effectively counteracted by glutathione [ 29 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our study did not find significant involvement of the glutathione antioxidant system in disc degeneration. In contrast, Bakirezer et al [ 12 ] and Gu et al [ 28 ] reported significantly lower serum glutathione levels in patients with LDD than in healthy individuals or in those with less degeneration. Additionally, an in vitro disc cell model showed that the harmful effects of hydrogen peroxide could be effectively counteracted by glutathione [ 29 ].…”
Section: Discussionmentioning
confidence: 93%